Characterization and exploitation of Lactobacillus strains as potential probiotics for humans and chickens - Shokryazdan, Parisa (2013)
Among the lactic acid bacteria, lactobacilli are the most common microorganisms used as probiotics. Many different strains of Lactobacillus have been reported to be suitable probiotics for different hosts and new strains are being discovered as potential candidates. It has been suggested that there are beneficial lactic acid bacterial strains in human milk and feces, fermented foods and chicken intestines which can be used as probiotics. Thus, this study was conducted to isolate, identify and characterize some new lactic acid bacterial strains from the above-mentioned sources with a view to exploit them as potential probiotics for humans and chickens. One hundred and eighty-two lactic acid bacterial strains were isolated and 12 strains which showed bile and acid tolerance (growth measured as cell turbidity) were selected and identified using carbohydrate fermentation patterns and 16S rRNA gene sequences. All 12 strains belonged to the genus Lactobacillus, of which three strains were L. buchneri, three were L. casei, one was L. acidophilus, two were L. fermentum and three were L. salivarius. The 12 Lactobacillus strains and two commercial reference strains, L. casei Shirota and L. reuteri C10, were tested for their ability to survive in the gastrointestinal tract using the following characteristics: tolerance to acid, bile salt and pancreatic enzyme (growth measured as viable counts of colony forming units [CFU]/ml) and adherence to intestinal cell line. The results showed that all 12 Lactobacillus strains were able to tolerate acid, bile and pancreatic enzyme. All 12 Lactobacillus strains also exhibited good adherence to the intestinal cell line (10.3 to 37.7 Lactobacillus cells per Caco-2 cell). In vitro assays on their bioactivities showed that all 12 Lactobacillus strains exhibited good antagonistic activity against a wide range of pathogens and most of the strains had significantly higher inhibitory effect against the pathogens than the two commercial reference strains. The antagonistic activity was due to production of organic acids. All strains also showed cholesterolreducing activity, good antioxidant activity and production of useful enzymes. The cholesterolreducing and antioxidant activities of many of the strains were significantly higher than those of the two commercial reference strains. Only three L. salivarius strains which were isolated from chicken intestines, and L. acidophilus HM1 isolated from human milk showed moderate to high BSH activity. None of the Lactobacillus strains produced harmful enzymes or biogenic amines. Three Lactobacillus strains (L. acidophilus HM1, L. fermentum HM3 and L. buchneri FD2) selected for their good adherence ability (33.5, 37.7 and 35.9 Lactobacillus cells per Caco-2 cell, respectively), and the commercial reference strain L. casei Shirota (19.7 Lactobacillus cells per Caco-2 cell) were investigated for their cytotoxic activity against three cancer cell lines and a normal cell line. The results showed that the three Lactobacillus strains showed selectivity in killing cancer cells when compared to the normal cells. However, the commercial reference strain, L. casei Shirota, did not show selectivity toward the cancer or normal cells. The efficacy of a mixture of three L. salivarius strains isolated from chicken intestines, which showed good probiotic traits, was evaluated in broiler chickens. The results revealed that the mixture of Lactobacillus strains significantly improved the body weight, body weight gain and feed conversion ratio, increased beneficial cecal bacteria such as lactobacilli and bifidobacteria, decreased harmful cecal bacteria such as E. coli and total aerobes, decreased serum total cholesterol, low density lipoprotein-cholesterol and triglycerides, reduced harmful cecal bacterial enzymes, β-glucosidase and β-glucuronidase, and improved the histomorphology of the gut by increasing villus heights and villus height:crypt depth ratio of broiler chickens. Two Lactobacillus strains (L. fermentum HM3 and L. buchneri FD2 isolated from human milk and fermented dates, respectively), with very good probiotic characteristics were selected as potential probiotic for humans and a safety assessment of them was carried out using acute and subacute oral toxicity tests in Sprague-Dawley rats. Results showed that both strains were safe and even at a high concentration of 1010 CFU/kg BW/day there were no observed adverse effects on growth, feed consumption, cellular blood components, serum biochemistry and vital organs of the animals fed Lactobacillus strains. The two Lactobacillus strains also increased beneficial cecal bacterial populations, and decreased pathogenic bacterial populations and harmful intestinal bacterial enzymes. In conclusion, all 12 Lactobacillus strains isolated in the present study showed good probiotic characteristics and bioactivities in vitro. In vivo study of three L. salivarius strains in broiler chickens indicated that they improved performance and well-being of chickens, and could be good probiotics for chickens, while toxicity tests on L. fermentum HM3 and L. buchneri FD2 in rats showed that they are safe, and could be further investigated and exploited as probiotics for humans.